A new C-anionic tripodal ligand 2-{bis(benzothiazolyl)(methoxy)methyl}phenyl and its bismuth complexes. Issue 23 (7th June 2021) - Shimada, Shigeru; Yin, Shuang-Feng; Bao, Ming
Abstract : A new tripodal carbon-anionic ligand, 2-{bis(benzothiazolyl)(methoxy)methyl}phenyl, was synthesized and used for the preparation of its bismuth complexes. Abstract : A new tripodal C-anionic ligand, 2-{bis(benzothiazolyl)(methoxy)methyl}phenyl (L), was stably generated by the reaction of the ligand precursor (L′), the corresponding bromide (2-BrC6 H4 )(MeO)C(C7 H4 NS)2 (C7 H4 NS = 2-benzothiazolyl), with n BuLi at −104 °C in the presence of TMEDA ( N, N, N ′, N ′-tetramethylethylenediamine). The ligand lithium salt reacted with BiCl3 to give a 2 : 1 complex L2 BiCl. A 1 : 1 complex LBiCl2 was obtained in good yield by the redistribution reaction between L2 BiCl and BiCl3 . X-ray diffraction analysis revealed that the ligand L coordinated in an expected κ 3 -C, N, N′ coordination mode in LBiCl2, while it coordinated in κ 3 -C, N, O and κ 2 -C, O coordination modes in L2 BiCl. The ligand precursor reacted with BiX3 (X = Cl, Br) to give 1 : 1 complexes L′BiX3 and was found to act as a neutral tripodal C(π), N, N-ligand.